2003
DOI: 10.1128/jvi.77.15.8584-8587.2003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Evolutionary Analysis of an Orangutan Foamy Virus

Abstract: The full-length proviral genome of a foamy virus infecting a Bornean orangutan was amplified, and its sequence was analyzed. Although the genome showed a clear resemblance to other published foamy virus genomes from apes and monkeys, phylogenetic analysis revealed that simian foamy virus SFVora was evolutionarily equidistant from foamy viruses from other hominoids and from those from Old World monkeys. This finding suggests an independent evolution within its host over a long period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…As illustrated schematically in Fig. 1D the YXXL motif is conserved between FV of different species and is duplicated in bovine FV and the recently characterized SFVora isolate (43). All primate FV isolates contain a PSAP motif, and a PPPX motif is found in all primate FV Gag proteins except for SFVagm, whereas both motifs are absent in FFV, bovine FV, and equine FV.…”
Section: Identification Of Late Domain Consensus Sequences In the Pfvmentioning
confidence: 99%
“…As illustrated schematically in Fig. 1D the YXXL motif is conserved between FV of different species and is duplicated in bovine FV and the recently characterized SFVora isolate (43). All primate FV isolates contain a PSAP motif, and a PPPX motif is found in all primate FV Gag proteins except for SFVagm, whereas both motifs are absent in FFV, bovine FV, and equine FV.…”
Section: Identification Of Late Domain Consensus Sequences In the Pfvmentioning
confidence: 99%
“…The recognition that AIDS originated as a zoonosis heightened public health concerns associated with infection of humans by other simian retroviruses endemic in non-human primates (NHPs) (Switzer et al, 2004). These retroviruses include several strains of simian immunodeficiency virus (SIV) (Hahn et al, 2000;Peeters et al, 2002), simian T-cell lymphotropic virus types 1, 2 and 3 (STLV-1/2/3) (Meertens & Gessain, 2003;Meertens et al, 2001) and simian foamy retroviruses (SFVs or spumaretroviruses) (Bieniasz et al, 1995;Broussard et al, 1997;Hussain et al, 2003;Switzer et al, 2004;Verschoor et al, 2003).…”
mentioning
confidence: 99%
“…This is a remarkable low rate of evolution for a virus with RT that is as error-prone as other retroviruses. It has been suggested that FV may replicate through clonal expansion, analogous to primate T-lymphotropic viruses (Leendertz et al, 2008;Verschoor et al, 2003), thereby avoiding the introduction of many RT-induced mutations over short timescales. However, although most tissues harbour latent provirus in naturally infected rhesus macaques, viral replication does take place in oral mucosa (Murray et al, 2008), which complicates an explanation of low evolutionary rates by clonal expansion.…”
mentioning
confidence: 99%
“…FV have been isolated and cloned from a variety of primate (for references see below) and non-primate hosts (Holzschu et al, 1998;Tobaly-Tapiero et al, 2000;Winkler et al, 1997). Evolutionary studies would benefit from the characterization of the FV genomic diversity, but to date, only a few primate FVs from macaques (SFVmac) (Kupiec et al, 1991), African green monkey (SFVagm) (Renne et al, 1992), orang-utan (SFVora) (Verschoor et al, 2003), chimpanzees (SFVcpz) (Herchenröder et al, 1994(Herchenröder et al, , 1995, spider monkey (SFVspm) (Thümer et al, 2007), marmoset and squirrel monkey (Pacheco et al, 2010) have been cloned and completely sequenced. Although the gorilla simian FV (SFVgor) has been previously isolated and partially sequenced (Bieniasz et al, 1995;Calattini et al, 2004Calattini et al, , 2007Wolfe et al, 2004), the complete sequence of the SFVgor represents the last missing piece of the FV genomic puzzle within the great apes.…”
mentioning
confidence: 99%